Body image and body change behaviors associated with orthorexia symptoms in males. (September 2020) - White, Mika; Berry, Rachel; Rodgers, Rachel F.
Highlights: This study symptoms of Orthorexia Nervosa and other facets of disordered eating among men. Orthorexia symptoms were associated with other eating disorder symptoms. Orthorexia symptoms were also associated with muscularity-oriented attitudes and behaviors. Abstract: In recent years, Orthorexia Nervosa has received increasing attention as a form of restrictive disordered eating driven by concerns related to "healthy eating" as opposed to weight and shape concerns. To date, however, data on the correlates of orthorexia in men are lacking, particularly pertaining to the relationship between orthorexia and muscularity-related dimensions. A sample of 103 ( Mage = 19.84) male college students completed an online questionnaire reporting on orthorexia symptoms, eating pathology, drive for muscularity, exercise dependence, and internalization of the thin and athletic ideals. Correlational analyses and linear regression models were used to explore relationships between orthorexia and variables of interest. Findings revealed positive relationships between high levels of orthorexia symptoms and eating pathology, exercise dependence, thin and athletic internalization, and behavioral dimensions of drive for muscularity. The results of this study extend our understanding of the correlates of orthorexia symptoms among young men and highlight their association with other dimensions of eating pathology as well as dysfunctional exercise. In addition, concerns related to healthiness may overlap with muscularity-related concerns, perhaps due to the conflation between health and muscular appearance in social constructions of male body ideals.